Analisis Fraud Pentagon dalam mendeteksi Financial Statement Fraud (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020) - Violita Maharani Anggraini; Atwal Arifin (STKIP NU Kabupaten Tegal, 2022)
Financial statement fraud is a fraudulent act of financial statements. The theory of pentagon fraud from Crowe Howarth (2011) has five elements namely pressure, opportunity, rationalization, capability, arrogance. This study was conducted to analyze the influence of pentagon fraud in detecting financial statament fraud in mining companies listed on the BEI for the periode 2017-2020. The sampling technique used purposive sampling method. The results show that external pressure, ineffective monitoring, the nature of the industry had an effect on financial statement fraud. Meanwhile, financial stability, change in auditor, change in director, and frequent number of CEO pic have no effect on financial statement fraud.